2010
DOI: 10.1128/cmr.00039-09
|View full text |Cite
|
Sign up to set email alerts
|

The GenusAeromonas: Taxonomy, Pathogenicity, and Infection

Abstract: SUMMARY Over the past decade, the genus Aeromonas has undergone a number of significant changes of practical importance to clinical microbiologists and scientists alike. In parallel with the molecular revolution in microbiology, several new species have been identified on a phylogenetic basis, and the genome of the type species, A. hydrophila ATCC 7966, has been sequenced. In addition to established disease associations, Aeromonas has been shown to be a significant cause of infections associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
1,812
2
60

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,638 publications
(1,910 citation statements)
references
References 283 publications
36
1,812
2
60
Order By: Relevance
“…The taxonomy of the genus Aeromonas is complex and accompanied with confusion and controversy (Janda and Abbott, 2010;Martinez-Murcia et al, 2011;Martino et al, 2011). At present, 24 validly published species in the genus Aeromonas have been reported Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The taxonomy of the genus Aeromonas is complex and accompanied with confusion and controversy (Janda and Abbott, 2010;Martinez-Murcia et al, 2011;Martino et al, 2011). At present, 24 validly published species in the genus Aeromonas have been reported Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most common human disease associated with Aeromonas infection is gastroenteritis with diarrhea symptoms. Among the 21 species that have been differentiated based on DNA-DNA hybridization, A. caviae, A. veronii biotype sobria and A. hydrophila are most commonly associated with human infections and account for more than 85% of all clinical isolates [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The most common human disease associated with Aeromonas infection is gastroenteritis with diarrhea symptoms. Among the 21 species that have been differentiated based on DNA-DNA hybridization, A. caviae, A. veronii biotype sobria and A. hydrophila are most commonly associated with human infections and account for more than 85% of all clinical isolates [1,2].Recently, it has been reported that infection with A. hydrophila induces apoptosis in macrophages [3,4]. Although the cytotoxicity by the bacteria is believed to enable the bacteria to evade eradication and clearance by the macrophages, the host proinflammatory responses triggered by the death of the macrophages remain unknown.…”
mentioning
confidence: 99%
“…These microorganisms can cause disease in peoikilothermic and homeothermic animals, including human (Cahill 1990). They are associated with hemorrhagic septicemia in freshwater fish (Janda & Abbott 2010) and gastroenteritis transmitted to humans by contact and consumption of contaminated meat and water (Abdullah et al 2003).…”
Section: Introductionmentioning
confidence: 99%